One-step stromal vascular fraction therapy in osteoarthritis with tropoelastin-enhanced autologous stromal vascular fraction gel - Yang, Junjun; Wang, Xin; Zeng, XueBao; Wang, Rong; Ma, Yanming; Fu, Zhenlan; Wan, Zu; Wang, Zhi; Yang, Liu; Chen, Guangxing; Gong, Xiaoyuan (Frontiers in Bioengineering and Biotechnology, 2024)
Background: Osteoarthritis (OA) is a debilitating degenerative joint disease, leading to significant pain and disability. Despite advancements, current regenerative therapies, such as mesenchymal stem cells (MSCs), face challenges in clinical efficacy and ethical considerations. This study aimed to evaluate the therapeutic potential of stromal vascular fraction gel (SVF-gel) in comparison to available treatments like hyaluronic acid (HA) and adipose-derived stem cells (ADSCs) and to assess the enhancement of this potential by incorporating tropoelastin (TE). Methods: We conducted a comparative laboratory study, establishing an indirect co-culture system using a Transwell assay to test the effects of HA, ADSCs, SVF-gel, and TE-SVF-gel on osteoarthritic articular chondrocytes (OACs). Chondrogenic and hypertrophic markers were assessed after a 72-hour co-culture. SVF-gel was harvested from rat subcutaneous abdominal adipose tissue, with its mechanical properties characterized. Cell viability was specifically analyzed for SVF-gel and TE-SVF-gel. The in vivo therapeutic effectiveness was further investigated in a rat model of OA, examining MSCs tracking, effects on cartilage matrix synthesis, osteophyte formation, and muscle weight changes. Results: Cell viability assays revealed that TE-SVF-gel maintained higher cell survival rates than SVF-gel. In comparison to the control, HA, and ADSCs groups, SVF-gel and TE-SVF-gel significantly upregulated the expression of chondrogenic markers COL 2, SOX-9, and ACAN and downregulated the hypertrophic marker COL 10 in OACs. The TE-SVF-gel showed further improved expression of chondrogenic markers and a greater decrease in COL 10 expression compared to SVF-gel alone. Notably, the TE-SVF-gel treated group in the in vivo OA model exhibited the most MSCs on the synovial surface, superior cartilage matrix synthesis, increased COL 2 expression, and better muscle weight recovery, despite the presence of fewer stem cells than other treatments. Discussion: The findings suggest that SVF-gel, particularly when combined with TE, provides a more effective regenerative treatment for OA by enhancing the therapeutic potential of MSCs. This combination could represent an innovative strategy that overcomes limitations of current therapies, offering a new avenue for patient treatment. Further research is warranted to explore the long-term benefits and potential clinical applications of this combined approach.